Leukocytosis as The Short-Term Predictor for Mortality in Acute Coronary Syndrome Patients Undergoing Percutaneous Coronary Intervention - Setyasih Anjarwani; Krishna Ari Nugraha; Muhammad Rizki Fadlan (Universitas Brawijaya, 2020)
AbstractBackground: In daily clinical practice, leukocyte count is the most common and simple inflammation parameter. Moreover, its role in predicting acute coronary syndrome (ACS) patients' clinical outcomes and prognosis is still conflicting. This study aimed to assess the role of leukocytosis as the predictor of mortality in ACS patients undergoing percutaneous coronary intervention (PCI).Method: This single-center retrospective cohort study used the STEMI registry data in Saiful Anwar General Hospital, Malang, Indonesia, from January to July 2019. The exposure was the leucocyte count during hospital admission and the outcome was the 30-day mortality following PCI procedure. The receiver-operating characteristic (ROC) curve was used to determine leucocyte count cut-off pint, sensitivity, and specificity.Result: The best leukocyte count cut-off value was 12300/µL, with the area under the curve (AUC) of 0.702 (95% CI 0.575 - 0.83), sensitivity of 71.4%, and specificity of 61.3%. Leukocytosis increased the risk of 30-day mortality (74.5% vs 42.4%; OR = 3.958; 95% CI = 1.518-10.25; p = 0.014). Survival rate within 30-day after PCI was lowered in leukocytosis group (the Log-Rank p = 0.002). The difference became apparent after day five post-PCI. Conclusion: Leukocytosis during hospital admission is associated with increased mortality in ACS patients undergoing PCI. Leucocytosis is a good predictor of mortality within 30 days after PCI in this population. Keywords: leukocytosis, acute coronary syndrome, percutaneous coronary intervention, mortality